Oncologic impact of concomitant prostate cancer characteristics at the time of radical cystoprostatectomy for bladder cancer: a population-based analysis. (31st December 2022) - Kachanov, Mykyta; Vetterlein, Malte W.; Soave, Armin; Karakiewicz, Pierre I.; Liakos, Nikolaos; Jankowski, Thomas; Pose, Randi M.; Mandrek, Mikolaj; Fisch, Margit; Witt, Jorn H.; Graefen, Markus; Leyh-Bannurah, Sami-Ramzi
Abstract: Objective: The aim of this study was to evaluate the prognostic impact of concomitant prostate cancer (PCa) of the cancer-specific mortality (CSM) in the aging patient's papulation with bladder cancer (BCa) treated with radical cystoprostatectomy (RCP). Materials and Methods: Within the SEER database (2004–2015), 1468 patients were treated with RCP for BCa harboring histopathological PCa findings. To account for other cause mortality (OCM), multivariable competing risk regression (CRR) tested for potential BCa-CSM differences according to PCa characteristics risk factors predicting CSM Results: CRR analysis revealed that only following BCa characteristics, as high pathological tumor stages(Ta/Tis/T1 [REF.] vs. T2; HR 2.03, 95% CI: 1.16-3.57, p = 0.014 vs. T3; HR 4.32, 95% CI: 2.45-7.61, p < 0.001 vs. T4; HR 5.06, 95% CI: 2.77–9.22, p < 0.001), as well unfavorable BCa grade IV (Grade I–II [REF.] vs. Grade IV; HR 0.58, 95% CI: 0.35-0.98, p < 0.041) achieved independent predictor status of CSM. With regard to PCa characteristics, none of the covariates yielded independent predictor status of CSM. Conclusions: Our study, based on the largest population cohort, demonstrates that even in organ-confined BCa patients, concomitant PCa as second malignancy does not represent a risk factor for survival.